2009
DOI: 10.1002/apj.339
|View full text |Cite
|
Sign up to set email alerts
|

Development of thin film composite for CO2 separation in membrane gas absorption application

Abstract: The thin film composite (TFC) membrane based on polypropylene (PP) and polyvinylidenefluoride (PVDF) was prepared using glutaraldehyde as the selective layer. The percentages of glutaraldehyde were optimized to maximize the permeability of carbon dioxide (CO 2 ) and selectivity as well. The TFC with 6% w/v of glutaraldehyde based on PVDF achieved the highest permeance of 881.70 GPU and 18.08 for selectivity through the increase in effective layer and skin layer thickness. This TFC promises to provide porous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…117 There are adsorption-selective NPCFs that separate the components of a gas mixture depending on their adsorption properties, and size-and shape-selective NPCFs that separate the components of a gas mixture depending on their pore sizes and shapes. [118][119][120][121][122][123] It was reported that NPCFs had high separation performance for air and for organic vapors of low molecular weight as well as for the dehydrogenation of cyclohexane to benzene. 124,125 For air separation, NPCFs performed well in terms of the ideal selectivity ratio for oxygen to nitrogen permeances of $3 to 6 and the oxygen permeance of 108 mol m À2 s À1 Pa À1 and in terms of relative insensitivity to operating temperature.…”
Section: Separation Membranesmentioning
confidence: 99%
“…117 There are adsorption-selective NPCFs that separate the components of a gas mixture depending on their adsorption properties, and size-and shape-selective NPCFs that separate the components of a gas mixture depending on their pore sizes and shapes. [118][119][120][121][122][123] It was reported that NPCFs had high separation performance for air and for organic vapors of low molecular weight as well as for the dehydrogenation of cyclohexane to benzene. 124,125 For air separation, NPCFs performed well in terms of the ideal selectivity ratio for oxygen to nitrogen permeances of $3 to 6 and the oxygen permeance of 108 mol m À2 s À1 Pa À1 and in terms of relative insensitivity to operating temperature.…”
Section: Separation Membranesmentioning
confidence: 99%
“…Temperature and feed pressure were controlled with an error of +/-0.1°C and 0.1 bar using MKS instrument temperature and feed pressure controllers, respectively. The gas permeation was calculated using equation (1), while ideal selectivity was calculated using equation (2) as follows [22,23].…”
Section: Permeation Studymentioning
confidence: 99%
“…A range of technologies to mitigate climate change by isolating a significant fraction of CO 2 from the atmosphere are pursued . The calcium looping technology for CO 2 capture in the context of continued utilization of coal in power plants is known as one promising technology .…”
Section: Introductionmentioning
confidence: 99%